Perbandingan Hasil Analisis Metode LoB (Line of Balance dan Metode PDM (Prescedence Diagram Method) dalam Penjadwalan Pembangunan Citra Agrindo III - Nadiva Eka Putri Gobel; Mohammad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
The rapid growth of population has significantly increased the demand for housing, leading to the acceleration of residential construction projects. In this context, the efficiency of project scheduling methods plays a critical role in ensuring timely delivery and optimal resource utilization. This study aims to compare the effectiveness of the Line of Balance (LoB) and the Precedence Diagram Method (PDM) in the construction of the Citra Agrindo III Housing project. Employing a descriptive approach and utilizing secondary data such as S-curves and project time schedules, the research provides a detailed analysis of each method’s strengths and limitations. The findings reveal that the PDM method results in a shorter project duration, completing construction in 119 days, which is 4 days faster than the LoB method, requiring 123 days. This indicates that PDM is more effective in projects where task dependencies and sequencing play a significant role, as it clearly maps the relationships between activities. On the other hand, LoB demonstrates its superiority in managing repetitive tasks, ensuring smoother resource allocation and workflow consistency across housing units. The results highlight that both methods possess distinct advantages depending on project characteristics. Thus, project managers are encouraged to select scheduling methods that align with the nature of the project to achieve greater efficiency in both time and cost management. This comparison contributes to the broader understanding of construction project management and provides practical insights for improving scheduling strategies in the residential sector.